52-(2c+4)=4(c+5)+c

Simple and best practice solution for 52-(2c+4)=4(c+5)+c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 52-(2c+4)=4(c+5)+c equation:


Simplifying
52 + -1(2c + 4) = 4(c + 5) + c

Reorder the terms:
52 + -1(4 + 2c) = 4(c + 5) + c
52 + (4 * -1 + 2c * -1) = 4(c + 5) + c
52 + (-4 + -2c) = 4(c + 5) + c

Combine like terms: 52 + -4 = 48
48 + -2c = 4(c + 5) + c

Reorder the terms:
48 + -2c = 4(5 + c) + c
48 + -2c = (5 * 4 + c * 4) + c
48 + -2c = (20 + 4c) + c

Combine like terms: 4c + c = 5c
48 + -2c = 20 + 5c

Solving
48 + -2c = 20 + 5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5c' to each side of the equation.
48 + -2c + -5c = 20 + 5c + -5c

Combine like terms: -2c + -5c = -7c
48 + -7c = 20 + 5c + -5c

Combine like terms: 5c + -5c = 0
48 + -7c = 20 + 0
48 + -7c = 20

Add '-48' to each side of the equation.
48 + -48 + -7c = 20 + -48

Combine like terms: 48 + -48 = 0
0 + -7c = 20 + -48
-7c = 20 + -48

Combine like terms: 20 + -48 = -28
-7c = -28

Divide each side by '-7'.
c = 4

Simplifying
c = 4

See similar equations:

| 104-5x=22x+17 | | -8*-7x=8 | | 52-(2c+4)=(c+5)+c | | 13y=12y-10 | | -7-5x=-5 | | 5(x-6)+2=7x-10 | | -2(x+4)+5=8(x+4)+8 | | 7a^2-11a+4=0 | | 2x+6=-33-7x | | 23c+234=23 | | 3a+2+a=34 | | 2x+3y+z=6 | | 5*-6x=-2 | | 3ln(2-3x)=0.5 | | -5*10x=-6 | | 47-7x=11+11x | | 8=7y-4(y-1) | | x^2+2-26=0 | | =10x-144 | | 13x-2(x-4)=8x+1 | | 4x-6(3-x)=9 | | (5x+6)-(2+2x)=0 | | x^2+8xy+12y^2=0 | | 5m-2(m+1)=-10 | | -5(1-2b)=20 | | -10-n=9 | | 32-6x=15+11x | | 2y-7y-4y=81 | | 6-7x=6x-8x-29 | | 6-n=-3 | | 5x+3y=10 | | 0.4x+0.8=0.2-0.2x |

Equations solver categories